Classroom-Based Assessment Practices and Challenges of Primary Teachers: Basis for A Proposed Upskilling Program - Bravo, Maricel M.; Paceno, Rosemarie D. (RIRAI Publisher, 2025)
The study explored the classroom-based assessment (CBA) practices and challenges of primary teachers in the West Butuan District as the basis for a proposed upskilling program. Employing a mixed-methods approach, the investigation utilized a validated survey questionnaire administered to 44 primary teachers, supplemented by a focus group discussion (FGD) to capture contextual and experiential insights. Quantitative data were analyzed using weighted mean and Spearman Rho correlation, while qualitative responses were thematically coded. Findings indicated that while primary teachers demonstrated a generally high level of knowledge in key CBA domains—Table of Specifications (TOS), item development, test administration, scoring, and item evaluation—gaps remained in the practical application of this knowledge, particularly in ensuring test coverage, managing assessment time, and conducting item analysis. Statistically significant correlations were found between knowledge in all five CBA domains and actual assessment practices. The FGD further revealed persistent challenges, including limited training in item evaluation, difficulty in constructing time-bound assessments, and misalignment between test items and instructional objectives. In response, a three-day face-to-face upskilling program was developed to address these gaps through collaborative workshops, real-time feedback, and hands-on output creation, with the goal of improving assessment quality, enhancing instructional planning, and promoting better learner outcomes.